COMPREHENSIVE ARABIC CURRICULUM: HARMONIZING MULTICULTURAL PERSPECTIVES, INTEGRATION AND ACTFL FOR A GLOBAL GENERATION - Khairanis, Retisfa; Aldi, Muhammad (Media Inovasi Pendidikan dan Pembelajaran, 2024)
This research aims to explore curriculum models that are appropriate for a country as diverse in social, cultural, political aspirations and economic capabilities as Indonesia. By focusing on multicultural, integration, and ACTFL (American Council on the Teaching of Foreign Languages) perspective curriculum models, this research seeks to identify solutions to improve the Arabic Education curriculum so that it can accommodate the needs of various parties and support the formation of superior generations in the future. The research used a qualitative approach with a descriptive-analytic design. Data were collected through in-depth interviews with education experts, curriculum developers, teachers and principals; participatory observation in schools; and document analysis of education policies and curriculum materials. Data were analyzed using thematic analysis techniques to identify key themes and link them to curriculum development theory. The results show that social and cultural diversity plays a significant role in determining the success of the curriculum. The multicultural curriculum model has great potential in accommodating such diversity, while the integration and ACTFL models contribute to the formation of synergies between general education, religion and foreign language learning. All three, if applied appropriately, can create a curriculum that is relevant, inclusive and adaptive to the needs of society. The implications of this research emphasize the importance of multiculturalism-based curriculum development to answer the challenges of diversity in Indonesia. The contribution of this research provides a basis for policy makers to design a curriculum that is not only academically relevant but also able to shape the character of a globally competitive young generation without ignoring local cultural roots. Keywords: Arabic Language Curriculum, Multicultural, Integration, ACTFL